Proceedings of the 16th Annual Joint Conference on Innovation and Technology in Computer Science Education 2011
DOI: 10.1145/1999747.1999768
|View full text |Cite
|
Sign up to set email alerts
|

A study in engaging female students in computer science using role models

Abstract: An effective approach to engaging young women to take computing in higher education is to provide examples of successful female computer scientists. Can a print publication that combines core computing concepts with inspiring stories of women in the field be effective? In this paper, we describe a campaign that distributed a 60-page booklet on women in computing to UK secondary schools. We analyse the initial response from teachers, and draw some general conclusions from the project. Teachers expressed strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…Hence, in recent years there have been many studies that have tried to reverse this trend and that have shown good results in terms of changing the image of this discipline and modifying the perception about the type of jobs that computer scientists hold: Workshops to show high school students the way computer scientists work [10], a campaign that distributed a booklet on women in computing to secondary schools [12], LEGO Mindstorms and App Inventor summer camps for high school girls [13,14], summer camps to emphasize possible careers that rely on computer technology [15], and numerous workshops [16,17] and summer camps [18,19] using Scratch programming environment.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, in recent years there have been many studies that have tried to reverse this trend and that have shown good results in terms of changing the image of this discipline and modifying the perception about the type of jobs that computer scientists hold: Workshops to show high school students the way computer scientists work [10], a campaign that distributed a booklet on women in computing to secondary schools [12], LEGO Mindstorms and App Inventor summer camps for high school girls [13,14], summer camps to emphasize possible careers that rely on computer technology [15], and numerous workshops [16,17] and summer camps [18,19] using Scratch programming environment.…”
Section: Related Workmentioning
confidence: 99%
“…There is essentially an imbalance between the genders in computing with a great under representation of girls enrolled in computing programs [1], [3], [15], [16]. Black et al [15] reports that women have mostly been a minority in computing; with female enrolment in computing undergraduate programs declining in many countries, with no promised change in sight.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Black et al [15] reports that women have mostly been a minority in computing; with female enrolment in computing undergraduate programs declining in many countries, with no promised change in sight.…”
Section: Gender Differencesmentioning
confidence: 99%
“…One of the major factors influencing this reality is suggested by research and widely recognized in CS education forums. It has been recognized that there are biases and negative perceptions that the population in general, the media and in particular high school students hold of CS [5,2,4,7,6,3]. As female university students and a female faculty member in CS, we are convinced that it is a worthwhile enterprise to demystify the negative perceptions about CS and about the role of women in CS so as to encourage more female students to pursue a career in CS.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of several very valuable initiatives that share our goals (e.g. [5,2,4].) Additionally, WICS activities and in particular Try/CATCH show that events run essentially by dedicated and responsible student volunteers make an impact and provide added benefits.…”
Section: Introductionmentioning
confidence: 99%